Integrated immunoinformatics and subtractive proteomics approach for multi-epitope vaccine designing to combat S. pneumoniae TIGR4 - Ashgar, Sami S.; Faidah, Hani; Bantun, Farkad; Jalal, Naif A.; Qusty, Naeem F.; Darwish, Abdulla; Haque, Shafiul; Janahi, Essam M. (Frontiers in Molecular Biosciences, 2023)
Streptococcus pneumoniae is one of the most dangerous pathogens and it causes over 1.2 million fatalities annually. It is capsulated and gram-positive bacterium with 2236 open reading frames. Around 101 serotypes have been discovered till now. The most common cause of respiratory infections, including pneumonia, meningitis, otitis media, and other disorders, is the clinically important bacterium S. pneumoniae. The most significant virulence element of pneumococci, the polysaccharide capsule, whose gene locus displays a similar arrangement in all strains, is what determines the pneumococcal serotypes. S. pneumoniae is prone to antibiotic resistance, capsular flipping, and ongoing genome change. Pneumococcus strain TIGR4's serotype causes bacteremia, meningitis, and pneumonia. The availability of ineffective vaccinations against specific serotypes and the rise in bacterial resistance make it difficult to treat diseases brought on by this pathogen. The clinically relevant serotype 4 strain of S. pneumoniae known as TIGR4, plays a noteworthy role in the pathogenesis of illnesses and infections of the respiratory tract. In this study immunoinformatics analysis was performed to construct a multi-epitope vaccine. The goal of this study is to develop a vaccine that uses a mix of immunological methods and molecular docking to target the highly antigenic proteins in S. pneumoniae. The core sequence of the vaccine's designing was used for homology modelling. The anticipated 3D structure was subjected to disulfide engineering to improve stability. The stability of the vaccine receptor complex and its binding relationship were investigated using molecular docking and dynamic modelling. In addition, immunological reactions brought on by the vaccination antigen were simulated to test real-world potency. The vaccine codon was then in-silico cloned. Further, in vitro and in vivo experimental validation studies are desired to ratify our current findings.